Ionic Liquids: A Simple Model to Predict Ion Conductivity Based on DFT Derived Physical Parameters - Nilsson-Hallén, Jonathan; Ahlström, Bodil; Marczewski, Maciej; Johansson, Patrik (Frontiers in Chemistry, 2019)
A model able to a priori predict ion conductivities of ionic liquids (ILs) is a desired design tool. We here propose a set of simple conductivity models for ILs composed of small ions by only using data easily derived from standard DFT calculations as input; ion volume, ion mass, ion moment of inertia, and the ion-ion interaction strenght. Hence these simple models are totally without any need for experimental parametrisation. All model are made from fits of 22 ILs based on 12 different cations and 5 different anions, resulting in correlations vs. experiment of R2≈0.95 and MAE of 25-36%. Given their (very) simple layout and how fast they can be applied (and re-used), the models allow for ample screening of new IL designs, while not aimed for perfect predictions per se.